The Effectiveness Of The Profetic Gestalt Approach (G-Pro) To Improve Student Tolerance - Fuzna Nur 'Aqilah; Endin Mujahidin (Prophetic guidance and counseling journal, 2020)
This research is a profetic Gestalt study (G-Pro) in improving the religious tolerance of students in IBN ' AQIL High School. The purpose of this study is to increase the religious tolerance of high school students by using an IT-based Gestalt profetic (G-Pro) guidance and counseling approach. This research uses a quantitative approach with the experimental quation method. The design of the research used is pretest-posttest design of the Nonequivalent group. The population of this study was 110 students at Senior High School (SMA) IBN ' AQIL. Research samples were taken 60 people from the population. A tool for measuring a poll. The data analysis used in this study is quantitative and inferential descriptive analysis. The results of the study known that the G-Pro approach to improving religious tolerance for students in SMA ibn ' Aqil is known Thitung > this (4,826 > 1,980), so it can be stated that there is a significant influence of religious tolerance of students on Group experiments and control groups or it can be said that groups of students given the approach of Gestalt profetic (G-Pro) guidance and counseling are better than those of the control group.